Atomistic Simulation of Intrinsic Defects and Trivalent and Tetravalent Ion Doping in Hydroxyapatite - Ricardo D. S. Santos; Marcos V. dos S. Rezende (Advances in Condensed Matter Physics)
Atomistic simulation techniques have been employed in order to investigate key issues related to intrinsic defects and a variety of dopants from trivalent and tetravalent ions. The most favorable intrinsic defect is determined to be a scheme involving calcium and hydroxyl vacancies. It is found that trivalent ions have an energetic preference for the Ca site, while tetravalent ions can enter P sites. Charge compensation is predicted to occur basically via three schemes. In general, the charge compensation via the formation of calcium vacancies is more favorable. Trivalent dopant ions are more stable than tetravalent dopants.